ESTIMATION OF GEOMETRIC PARAMETERS OF THE POLE SYSTEM OF MATRIX OF ELECTROMAGNETIC SEPARATOR - SHVEDCHYKOVA, IRYNA; ROMANCHENKO, JULIA; MELKONOVA, INNA (Technologies and Engineering, 2022)
Purpose. The choice of the geometric dimensions ratios of system of matrix poles of electromagnetic polygradient separator to increase productivity with maintaining the reliability of extracting of ferromagnetic impurities from bulk material. Methodology. To solve the dynamic problem of motion of a ferromagnetic body in the working gap of pole system of matrix of polygradient separator under the influence of an external magnetic field the known methods of solving linear inhomogeneous differential equations are used. To confirm the reliability of obtained results the method of experimental research is used. Findings. The formulation of dynamic problem of movement of ferromagnetic body in the working gap of plate pole system of matrix of polygradient separator is carried out. Parametric equation for the trajectory of ferromagnetic body removal and a calculated relation connecting the main geometric dimensions of the system of matrix poles are obtained. The calculation results are confirmed experimentally and by operating practice of known magnetic separating devices. Originality. The mathematical description of working process of a polygradient electromagnetic separator with a plate matrix was further developed, which made it possible to obtain an analytical expression that takes into account the main geometric dimensions of the working space of matrix of separator. Practical value. Accounting of obtained analytical dependences between the length of separation zone and air gap, which characterizes the thickness of the separated material layer through which the ferromagnetic body must pass during the separation process, will ensure the necessary purity and productivity of separation.